Public private partnerships - Ramesh, G. (New York : Routledge, 2010)
Contributed articles.
section 1. Structure of PPP -- section 2. Governance of PPP -- section 3. Global learning -- section 4. Financing PPP in infrastructure -- section 5. PPP in services and utilities.
Includes bibliographical references.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Public-private sector cooperation; Electronic books